High-oil-resistance wide-temperature-range fluorosilicone rubber composite material, preparation method and application
Through the development of high oil-resistant and wide temperature domain fluorosilic rubber composite materials, combined with specific process processing, the problems of insufficient sealing performance and oil resistance of existing rubber materials in high and low temperature environments are solved, and excellent sealing in wide temperature domains are achieved Performance, suitable for sealing applications in the aerospace field.
Patent Information
- Application Number
- CN202411490088.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing rubber materials have poor sealing performance in high and low temperature environments and lack oil resistance, making it difficult to meet the strict conditions in the aerospace field.
The high oil-resistant and wide temperature domain fluorosilicone rubber composite material is used to improve the modulus and oil resistance of the material through the combination of fluorosilicone rubber master glue, reinforcement filler, vulcanizing agent and structured control agent.
It has achieved long-term use in the range of -55℃~200℃, with excellent sealing performance and low temperature retraction temperature, and is suitable for sealing parts in the aerospace field.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and specifically relates to a high-oil-resistant and wide-temperature-range fluorosilicone rubber composite material, a preparation method and applications thereof. Background Art
[0002] In aircraft hydraulic systems, rubber-plastic combination seals are a common form of external dynamic seals, often used in the actuators of aircraft actuation systems, where the rubber ring provides elastic preload, and the plastic slip ring is in direct contact with the moving shaft to form the main working surface. During the working process, the seal ring is inevitably worn on the contact surface under the dual effects of pre-compression and oil pressure. With the continuous loss of seal ring material, the sealing effect will decrease and the leakage will increase. Severe leakage will cause system function failure and even threaten flight safety. Therefore, the slip ring of the rubber-plastic combination seal ring is generally made of modified polytetrafluoroethylene material with a lower friction coefficient. After wear, it can maintain a good fit with the shaft by relying on the elastic force provided by the rubber ring. For the rubber seal ring material, its main function is to prevent the leakage of hydraulic oil. It not only needs to be used for a long time in the aviation hydraulic oil environment, but also needs to have good high and low temperature capabilities. If the seal fails and causes hydraulic oil leakage, it will bring many hazards. At the least, it will pollute the body environment and reduce the working capacity of hydraulic equipment and components. At the worst, the power loss of the hydraulic system will be too large, causing an aircraft accident.
[0003] At present, the main rubber materials used for hydraulic seals are as follows: Nitrile rubber (NBR): NBR seals will age quickly when working for a long time at 135°C. At the same time, thermal expansion will also cause the compression of the seal to increase, thereby increasing the permanent deformation. Under low temperature conditions of -55°C, the low-temperature crystallization of the rubber material will reduce the flexibility of the rubber molecular chain and the elasticity, resulting in reduced reliability of the seal (Lei Haijun, Zhang Jizhong, Gong Wenfeng, etc. Wide temperature range 15 # Research on the performance of fluorosilicone rubber for aviation hydraulic oil [J]. Rubber Science and Technology, 2022, 20(03): 122-125.); Fluororubber: Fluororubber is a binary and ternary elastomer composed of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene. Fluororubber belongs to carbon chain saturated polar rubber. Its high temperature resistance and oil resistance are the best among rubber materials, but its elasticity is poor, and its low temperature resistance and resistance to polar substances such as water are not ideal. Its brittle temperature is mostly between -20~-30℃ (Liu Li, Ma Tingchun, Li Shaoxiang, et al. Research progress of low temperature oil-resistant rubber [J]. Elastomer, 2008, (02): 69-74.); Fluoroether rubber: Fluoroether rubber introduces ether bonds on the side chains of fluororubber, destroys the regularity of the molecular chain, increases the flexibility of the molecular chain, and thus improves its low temperature resistance, but the low temperature shrinkage TR of fluoroether rubber 10Although the performance has dropped to around -30°C (Chen Yulin, Zhang Hao, Xu Rongyun, et al. Research on aramid pulp reinforced carbon black / fluoroether rubber composites [J]. Rubber Industry, 2023, 70(12): 949-953), it is still unable to meet the harsh conditions of high-altitude operating temperatures of aircraft reaching -55°C; Perfluoroether rubber: Perfluoroether rubber is usually polymerized from a variety of monomers, including tetrafluoroethylene (TFE), third vulcanization point monomer (CSM) and perfluoroalkyl (oxy) vinyl ether (PAVE / PAAVE). The introduction of vinyl ether makes the molecular chain of perfluoroether rubber more flexible, thereby greatly improving the low-temperature resistance of the material. The lowest operating temperature of perfluoroether rubber has dropped to -45°C, and it cannot perform oil-resistant sealing work for a long time in the extreme environment of aerospace. (Wang Baocheng, Zhang Bo, Wei Yuansi, et al. Research progress of perfluoroether rubber sealing materials [J / OL]. Lubrication and Sealing, 1-10 [2024-08-13]), and the current price of perfluoroether rubber is high, the price of each kilogram of raw rubber can reach tens of thousands of yuan, and the research and application of perfluoroether rubber needs further development.
[0004] Fluorosilicone rubber not only has the excellent high and low temperature performance of silicone rubber, but also has excellent oil resistance, solvent resistance (including aliphatic, aromatic and chlorinated solvents, etc.), and chemical resistance due to the introduction of fluorine. Therefore, it is now widely used in the field of aircraft and aeroengines. Moreover, fluorosilicone rubber is the only oil-resistant elastomer that can remain usable in the range of -68℃ to 232℃.
[0005] In the structure of the combined sealing ring, the rubber ring needs to have a high preload force on the plastic slip ring so as to provide a high uniform axial stress, achieve a high fit between the slip ring and the rotating shaft, and ensure the sealing function. Compared with nitrile rubber and fluoroether rubber, the mechanical properties of fluorosilicone rubber such as modulus (usually characterized by 100% elongation stress) and hardness are lower, which is why fluorosilicone rubber is rarely used in dynamic sealing conditions (Lu Ming, An Xiaopeng, Pang Bo, et al. Comparative study on the adaptability of several rubber materials to aviation hydraulic seals [J]. Aging and Application of Synthetic Materials, 2023, 52(06): 22-23+132).
[0006] Therefore, a rubber material with high oil resistance, wide temperature range and high modulus is needed to solve the above problems. Summary of the invention
[0007] In order to solve the above problems, a main purpose of the present invention is to provide a highly oil-resistant and wide-temperature-range fluorosilicone rubber composite material, which has excellent oil-resistant sealing performance, can be used for a long time in a wide temperature range of -55°C to 200°C, and has a high modulus.
[0008] In order to achieve the above-mentioned object, the present invention provides a high oil-resistant and wide temperature range fluorosilicone rubber composite material, the fluorosilicone rubber composite material comprising the following raw materials in parts by weight: 100 parts of fluorosilicone rubber masterbatch, 5 to 20 parts of reinforcing filler, 0.5 to 2 parts of vulcanizing agent, and 0.5 to 3 parts of structuring control agent.
[0009] Preferably, it also includes 0.5 to 3 parts of a processing aid, 0.5 to 3 parts of a silane coupling agent, and 0.1 to 0.5 parts of a vulcanizing agent or more.
[0010] Preferably, the fluorosilicone raw rubber is a fluorosilicone rubber prepared from a copolymer of 3,3,3-trifluoropropylmethylsiloxane chain segments and methylvinylsiloxane chain segments, and the fluorosilicone rubber masterbatch is a fluorosilicone rubber masterbatch prepared by blending fluorosilicone raw rubber, inorganic filler and silicone rubber.
[0011] Preferably, the reinforcing filler can be one or more of precipitated silica VN3, fumed silica A200, fumed silica R974, carbon black N330, carbon black N550, carbon black N774, carbon black N990, clay, calcium carbonate, and nano-light calcium carbonate. Among them, fumed silica A200 and fumed silica R974 are the best. The preferred addition amount is 10 to 15 parts by mass. Among them, the specific surface area of precipitated silica VN3 is 175m 2 / g; the average particle size of fumed silica A200 is 12nm, and the specific surface area is 175~225m 2 / g; the average particle size of fumed silica R974 is 16nm, and the specific surface area is 90~190m 2 / g; the particle size of carbon black N330 is 26~30nm; the particle size of carbon black N550 is 40~48nm; the particle size of carbon black N774 is 61~100nm; the particle size of carbon black N990 is 201~500nm.
[0012] Preferably, the vulcanizing agent is selected from at least one of dibenzoyl peroxide (DCP), 2,4-dichlorobenzoyl peroxide (DCBP) and 1,1-di-tert-butylperoxy-3,3,5-trimethoxycyclohexane (3M).
[0013] Preferably, the co-vulcanizing agent is at least one of triallyl cyanurate (TAC) and triallyl isocyanurate (TAIC).
[0014] Preferably, the silane coupling agent is one or more of vinyl triethoxy silane (A151), 3-(methacryloyloxy)propyl trimethoxy silane (A174), and octyl triethoxy silane (A137).
[0015] Another object of the present invention is to provide a method for preparing a highly oil-resistant and wide-temperature-range fluorosilicone rubber composite material, the method for preparing the composite material comprising: S1 pretreatment: adding the structure control agent to the reinforcing filler and preliminarily mixing; S2 mixing: put the fluorosilicone rubber masterbatch and the pretreated reinforcing filler into a kneader and knead them under closed conditions. The kneading time is 10-25 minutes, the kneader speed is 60-100 r / min, the temperature is 130-140°C, and then the vulcanizing agent is added. The dispersion time is 10 minutes to obtain a mixed rubber; S3 secondary mixing: after the rubber mix obtained in the kneading machine is taken out, a secondary mixing operation is performed on an open rubber mixer. The secondary mixing operation includes thinning and triangular wrapping the rubber mix on the open rubber mixer. The roller distance is 0.1-2 mm, and the number of times is 1-2 times and 3-5 times respectively. Then the roller distance of the open rubber mixer is increased to 1-2 mm, and the roll is rolled out 3-4 times; S4 vulcanization: the mixed rubber after the secondary mixing is placed at room temperature for 16 hours and then vulcanized at a vulcanization temperature of 170°C. At this vulcanization temperature, the vulcanization time is 7 minutes and the vulcanization pressure is 15 MPa to obtain a vulcanized rubber; S5 secondary vulcanization: performing secondary vulcanization treatment on the vulcanized rubber, the secondary vulcanization temperature is 200° C., at this temperature, the secondary vulcanization time is 4 hours, and the fluorosilicone rubber composite material is obtained.
[0016] Preferably, in the S1 pretreatment step, a silane coupling agent is added together with a structuring control agent to the reinforcing filler and preliminarily mixed; and / or, in the S2 mixing step, a processing aid is added together with the fluorosilicone rubber masterbatch and the pretreated reinforcing filler is put into a kneader for kneading; and / or, in the S2 mixing step, a vulcanizing agent is added while a vulcanizing agent is added.
[0017] The third object of the present invention is to provide an application of a high oil-resistant wide temperature range fluorosilicone rubber composite material in a rubber-plastic combined oil-resistant sealing structure. In the present invention, this sealing system is mainly used in engine seals, fuel system seals, hydraulic system seals, dynamic surface seals, etc. on aircraft in the aerospace field.
[0018] Compared with the prior art, the present invention has the following beneficial effects: The components of the high oil-resistant wide temperature range fluorosilicone rubber composite material provided by the present invention cooperate to precisely control the proportion of each component, thereby improving the comprehensive performance of fluorosilicone rubber, improving the modulus (tensile stress) and hardness of the material, and can be applied to combined sealing structures; the compression permanent deformation of the material under extreme high temperature (175°C) and high temperature oil-resistant environment (150°C@test oil in accordance with AMS3021 standard) is kept at a low level (compression permanent deformation rate does not exceed 20%), indicating that the material has excellent sealing performance, and the material has excellent low temperature performance (low temperature shrinkage temperature TR10 reaches -61.3°C), indicating that the material has the ability to work stably for a long time in an extremely low temperature (about -55°C) environment, and will not lose rubber elasticity or crack due to excessively low temperature. The rubber-plastic combined oil-resistant sealing structure made of the high oil-resistant wide temperature range fluorosilicone rubber composite material can be applied to engine seals, fuel system seals, hydraulic system seals, dynamic surface seals, etc. on aircraft in the aerospace field. DETAILED DESCRIPTION
[0019] The present invention is further described below in conjunction with actual cases, but the present invention is not limited to these embodiments.
[0020] In the present invention, in order to realize the applicability of the rubber material to aviation hydraulic oil, the oil resistant environment test of the composite material uses oils that meet the AMS3021 standard, which can test the ability of rubber to resist the penetration of diester polar compounds.
[0021] The fluorosilicone rubber masterbatch, vulcanizing agent, structuring control agent, processing aid, reinforcing filler, silane coupling agent and vulcanizing aid etc. used are all commercially available products.
[0022] Fluorosilicone rubber masterbatch is a fluorosilicone rubber masterbatch prepared by blending fluorosilicone raw rubber, inorganic filler and silicone rubber; the fluorosilicone raw rubber is a fluorosilicone rubber prepared by a copolymer of 3,3,3-trifluoropropylmethylsiloxane chain segments and methylvinylsiloxane chain segments.
[0023] In the following examples and comparative examples, the vulcanizing agent 5-bis(tert-butylperoxy)hexane (DBPH) is abbreviated as vulcanizing agent DBPH, the co-vulcanizing agent triallyl isocyanurate (TAIC) is abbreviated as co-vulcanizing agent TAIC, and the silane coupling agent vinyl triethoxysilane (A151) is abbreviated as silane coupling agent A151.
[0024] In the examples and comparative examples, hydroxy fluorosilicone oil was selected as the structuring control agent.
[0025] Example 1 The preparation method mainly comprises the following steps: S1 pretreatment: dry-modify the reinforcing filler fumed silica in advance, add the structural control agent hydroxyfluorosilicone oil into the reinforcing filler for premixing, and coat the surface of the reinforcing filler with the hydroxyfluorosilicone oil.
[0026] S2 Mixing: First, knead the fluorosilicone rubber masterbatch in a closed condition in a kneader for 1 minute, then add the pretreated reinforcing filler several times, the kneader speed is set to 80r / min, the high temperature kneading temperature is 130℃, the pretreated reinforcing filler is added in two stages, 3 / 4 of the total amount of reinforcing filler is added for the first time and mixed for 5 minutes, then the remaining reinforcing filler is added and mixed for 5 minutes, and the upper top plug is opened intermittently during the two mixing processes for 0.5 minutes and then closed. Reduce the temperature of the rubber in the kneader, then add the vulcanizer, knead for 2 minutes, and take out the mixed rubber.
[0027] S3 secondary mixing: The mixed rubber is taken out and subjected to multiple thin-pass and triangle-wrapped operations on an open rubber mixer, with a roller pitch of 0.1~2mm, for 1~2 times and 3~5 times respectively. Then the roller pitch of the open rubber mixer is increased to 1~2mm, and the rolls are rolled out for 3~4 times.
[0028] S4 vulcanization: After the secondary mixing, the mixed rubber was placed at room temperature for 16 hours, and then vulcanized using a flat plate vulcanizer. The vulcanization pressure was 15 MPa, the vulcanization temperature was set to 170°C, and the vulcanization time was 7 minutes.
[0029] S5 secondary vulcanization: The vulcanized rubber is subjected to secondary vulcanization at 200°C for 4 hours in a blast dryer and then placed at room temperature for 24 hours before use.
[0030] in, Fluorosilicone rubber masterbatch: 100g; Fumed silica A200 or R974: 13g; Hydroxyfluorosilicone oil: 2.5g; Curing agent DBPH: 1g.
[0031] Example 2 After pretreatment, mixing, secondary mixing, vulcanization, and secondary vulcanization according to the preparation method and conditions of Example 1, the difference of this embodiment is that the amount of reinforcing filler fumed white carbon ash is 10 mass fractions.
[0032] in, Fluorosilicone rubber masterbatch: 100g; Fumed silica A200 or R97: 10g; Hydroxyfluorosilicone oil: 2g; Curing agent DBPH: 1g.
[0033] Example 3 The difference between this embodiment and embodiment 2 is that the vulcanizing agent TAIC is added during the mixing process. In step S2, the vulcanizing agent is added at the same time as the vulcanizing agent. The other operating steps of this embodiment are the same as those of embodiment 2. in, Fluorosilicone rubber masterbatch: 100g; Fumed silica A200 or R97: 10g; Hydroxyfluorosilicone oil: 2g; Curing agent DBPH: 1g; Vulcanizing agent TAIC: 0.1g.
[0034] Example 4 The preparation method mainly comprises the following steps: S1 pretreatment: dry-modify the reinforcing filler fumed silica in advance, add hydroxy fluorosilicone oil into the reinforcing filler and premix it so that it is evenly coated on the surface of the reinforcing filler.
[0035] S2 Mixing: First, knead the fluorosilicone rubber masterbatch and the processing aid microcrystalline wax in a closed kneader for 1 minute, then add the treated reinforcing filler several times, the kneader speed is set to 80r / min, the high temperature kneading temperature is 130℃, the filler is added in two stages, 3 / 4 of the total amount of filler is added for the first time and mixed for 5 minutes, then the remaining filler is added and mixed for 5 minutes, and the upper top plug is opened intermittently during the two mixing processes, and then the upper top plug is closed after being kept for 0.5 minutes. Reduce the temperature of the rubber in the kneader, then add the vulcanizer, knead for 2 minutes, and take out the mixed rubber.
[0036] S3 secondary mixing: The mixed rubber is taken out and subjected to multiple thin-pass and triangle-wrapped operations on an open rubber mixer, with a roller pitch of 0.1~2mm, for 1~2 times and 3~5 times respectively. Then the roller pitch of the open rubber mixer is increased to 1~2mm, and the rolls are rolled out for 3~4 times.
[0037] S4 vulcanization: After the mixed rubber is placed at room temperature for 16 hours, it is vulcanized using a flat plate vulcanizer. The vulcanization pressure is 15MPa, the vulcanization temperature is set to 170℃, and the vulcanization time is 7min.
[0038] S5 secondary vulcanization: The vulcanized rubber is subjected to secondary vulcanization at 200°C for 4 hours in a blast dryer and placed at room temperature for 24 hours before use.
[0039] The difference between this embodiment and embodiment 2 is that in this embodiment, the fluorosilicone rubber masterbatch and the processing aid microcrystalline wax are first mixed and dispersed during the mixing process.
[0040] in, Fluorosilicone rubber masterbatch: 100g; Fumed silica A200 or R97: 10g; Hydroxyfluorosilicone oil: 2g; Curing agent DBPH: 1g; Microcrystalline wax: 2g.
[0041] Example 5 The preparation method mainly comprises the following steps: S1 pretreatment: dry-modify the reinforcing filler fumed silica in advance, add the structural control agent hydroxyfluorosilicone oil into the reinforcing filler for preliminary mixing, so that the hydroxyfluorosilicone oil is coated on the surface of the reinforcing filler.
[0042] S2 Mixing: First, knead the fluorosilicone rubber masterbatch in a closed kneader for 1 minute, then add the pretreated reinforcing filler in several times, set the kneader speed to 80r / min, the high temperature kneading temperature to 130℃, add the pretreated reinforcing filler in one step, and mix for 5 minutes. During the mixing process, open the top plug for 0.5 minutes and then close the top plug. After lowering the temperature of the rubber in the kneader, add the vulcanizer, continue kneading for 2 minutes, and then take out the mixed rubber.
[0043] S3 secondary mixing: The mixed rubber is taken out and subjected to multiple thin-pass and triangle-wrapped operations on an open rubber mixer, with a roller pitch of 0.1~2mm, for 1~2 times and 3~5 times respectively. Then the roller pitch of the open rubber mixer is increased to 1~2mm, and the rolls are rolled out for 3~4 times.
[0044] S4 vulcanization: After the mixed rubber is placed at room temperature for 16 hours, it is vulcanized using a flat plate vulcanizer. The vulcanization pressure is 15MPa, the vulcanization temperature is set to 170℃, and the vulcanization time is 7min.
[0045] S5 secondary vulcanization: The vulcanized rubber is subjected to secondary vulcanization at 200°C for 4 hours in a blast dryer and placed at room temperature for 24 hours before use.
[0046] The difference between this embodiment and embodiment 2 is that the mixing step S2 of this embodiment adopts a one-stage addition.
[0047] in, Fluorosilicone rubber masterbatch: 100g; Fumed silica A200 or R97: 10g; Hydroxyfluorosilicone oil: 2g; Curing agent DBPH: 1g.
[0048] Example 6 The difference between this embodiment and embodiment 2 is that in the S1 pretreatment step, the silane coupling agent A151 and the structure control agent are added together with the reinforcing filler and mixed.
[0049] in, Fluorosilicone rubber masterbatch: 100g; Fumed silica A200 or R97: 10g; Silane coupling agent 1g; Hydroxyfluorosilicone oil: 1g; Curing agent DBPH: 1g; Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, 8 parts by mass of fumed silica are added in the S1 pretreatment step.
[0050] in, Fluorosilicone rubber masterbatch: 100g; Fumed silica A200 or R97: 8g; Hydroxyfluorosilicone oil: 1.5g; Curing agent DBPH: 1g.
[0051] Comparative Example 2 The difference between this comparative example and Example 2 is that the structure control agent hydroxy fluorosilicone oil is not added and the S1 pretreatment step is not performed.
[0052] Fluorosilicone rubber masterbatch: 100g; Fumed silica A200 or R97: 10g; Curing agent DBPH: 1g.
[0053] Comparative Example 3 The difference between this comparative example and Example 3 is that the mass fraction of the vulcanizing agent TAIC added in this comparative example is increased to 0.2 parts.
[0054] in, Fluorosilicone rubber masterbatch: 100g; Fumed silica A200 or R97: 10g; Hydroxyfluorosilicone oil: 2g; Curing agent DBPH: 1g; Vulcanizing agent TAIC: 0.2g.
[0055] Comparative Example 4 The difference between this comparative example and Example 3 is that the mass fraction of the vulcanizing agent TAIC added in this comparative example is increased to 0.3 parts.
[0056] in, Fluorosilicone rubber masterbatch: 100g; Fumed silica A200 or R97: 10g; Hydroxyfluorosilicone oil: 2g; Curing agent DBPH: 1g; Vulcanizing agent TAIC: 0.3g.
[0057] Comparative Example 5 The difference between this comparative example and Example 4 is that the processing aid is replaced by stearic acid.
[0058] Fluorosilicone rubber masterbatch: 100g; Fumed silica A200 or R97: 10g; Hydroxyfluorosilicone oil: 2g; Curing agent DBPH: 1g; Stearic acid: 2g.
[0059] Comparative Example 6 The difference between this comparative example and Example 4 is that the processing aid is replaced by stearic acid and zinc oxide.
[0060] Fluorosilicone rubber masterbatch: 100g; Fumed silica A200 or R97: 10g; Hydroxyfluorosilicone oil: 2g; Curing agent DBPH: 1g; Stearic acid: 2g; Zinc oxide: 3g.
[0061] Comparative Example 7 The difference between this comparative example and Example 5 is that the kneading machine speed is set to 60 r / min during the mixing process, and the kneading temperature is 111°C.
[0062] in, Fluorosilicone rubber masterbatch: 100g; Fumed silica A200 or R97: 10g; Hydroxyfluorosilicone oil: 2g; Curing agent DBPH: 1g.
[0063] Comparative Example 8 The difference between this comparative example and Example 5 is that the kneading machine speed is set to 100 r / min during the mixing process, and the kneading temperature is 150°C.
[0064] in, Fluorosilicone rubber masterbatch: 100g; Fumed silica A200 or R97: 10g; Hydroxyfluorosilicone oil: 2g; Curing agent DBPH: 1g.
[0065] The purpose of pre-treating the hydroxyfluorosilicone oil and the silane coupling agent in S1 is to reduce the sliding of the rubber in the closed cavity during the kneading process, thereby affecting the kneading effect. Under the action of closed high temperature, it is beneficial to the slippage of the hydroxyfluorosilicone oil within the molecule and the combination of the hydroxyl group with the inorganic filler and the rubber molecular chain, which is beneficial to the dehydration and bonding effect of the silane coupling agent on the inorganic filler.
[0066] The function of the closed kneader in S2 is to mix and disperse the base rubber with reinforcing fillers, processing aids, vulcanizers and other additives (co-vulcanizers) to form a rubber composite material compound. In this process, the temperature needs to be strictly controlled. Below 130°C, the dispersion effect of the structural control agent on the inorganic filler is poor, and the filler is prone to agglomeration. Within 130~140°C, the dispersibility of the inorganic filler is effectively improved, and the prepared material has higher performance. Above 140°C, the fluorosilicone rubber molecular chain is more prone to defects under high temperature and high shear, the torque of the compound in the closed cavity of the kneader increases sharply, the dispersibility of the inorganic filler deteriorates, and a larger granular feel appears on the surface of the compound product, and the material performance deteriorates. During the research, it was found that the tensile strength of the material prepared at a mixing temperature of 131°C was 11.5% and 18.4% higher than that of the material prepared at a mixing temperature of 111°C and 150°C, and the elongation at break was 12.0% and 14.8% higher, respectively. Moreover, the tensile strength of the material prepared at a mixing temperature of 131°C was 5.7% higher than that of the material prepared at a mixing temperature of 111°C and 150°C, and the elongation at break was 6.3% higher than that of the material prepared at a mixing temperature of 150°C. This shows that the appropriate mixing temperature, mixing time and feeding method are helpful to improve the performance of the material.
[0067] At the same time, the order of adding materials needs to be strictly controlled. The order of adding materials in the kneading machine is as follows: fluorosilicone rubber masterbatch, silicone rubber masterbatch or silicone rubber raw rubber or fluorosilicone rubber raw rubber, processing aids, inorganic nano-reinforcing fillers and structuring control agents, as well as silane coupling agents, vulcanizers and vulcanizing aids.
[0068] In S3, the secondary mixing operation generally includes adjusting the roller distance of the mixed rubber on an open rubber mixer to between 0.1 mm and 2 mm, and performing multiple thin-pass, triangle-wrapping and rolling operations on the mixed rubber to further disperse the filler.
[0069] In S4, the vulcanization process can adopt any existing fluorosilicone rubber vulcanization process. Specifically, the vulcanization temperature can be 140-200°C, preferably 160-180°C; the vulcanization time can be 5-30 minutes, preferably 5-10 minutes. In one embodiment of the present invention, the vulcanization temperature is 170°C and the vulcanization time is 7 minutes.
[0070] In S5, the purpose of secondary vulcanization of the vulcanized rubber is to improve the vulcanization cross-linking structure and optimize the material properties. At the same time, the secondary vulcanization process is also conducive to removing the gas by-products and volatile substances generated during the vulcanization process to prevent them from affecting the material properties. After research, it was found that after the secondary vulcanization process, the tensile strength of the material increased by 15.3%, and the elongation at break was less affected, decreasing by 3%, which shows that the secondary vulcanization process has a significant enhancement on the mechanical properties of the material. The temperature of the secondary vulcanization can be at any temperature of 170~250℃, preferably 200~240℃, and the time of the secondary vulcanization can be any condition of 2h~8h, preferably 4h~6h. In some examples of the present invention, the secondary vulcanization treatment temperature is 200℃ and the secondary vulcanization time is 4h. The heating instrument is preferably a blast dryer. If a vacuum dryer is used, some small molecules in the material may be evaporated, resulting in a decrease in material performance.
[0071] The fluorosilicone rubber composite materials prepared in Examples 1-6 and Comparative Examples 1-8 were tested.
[0072] The test method is as follows: Hardness: According to the provisions of GB / T 531.1-2008, the test temperature is the standard laboratory temperature. The Shore A durometer, model BS61 Ⅱ, produced by German Bareiss Instruments, is used to measure the hardness of vulcanized rubber. The thickness of the sample is at least 6 mm. The measurement position of the Shore A durometer is at least 12 mm away from any edge. The standard spring test force is maintained for 3 seconds. Five measurements are made at different positions of the sample and the median value is taken.
[0073] Mechanical properties: According to the provisions of GB / T 528-2009, the specimen is a dumbbell-shaped type 1 standard specimen (the width of the narrow part is 6 mm), the test temperature is the standard laboratory temperature, and the mechanical properties of the dumbbell-shaped specimen are tested on an electronic universal testing machine (model AI-7000S1) produced by High Speed Rail Testing Instruments (Dongguan) Co., Ltd. The moving speed of the clamp is 500 mm / min, the number of measured specimens is 5, and the median of the measurement result is taken.
[0074] Compression set: According to the provisions of GB / T 7759.1-2015, a cylindrical specimen with a diameter of (29.0±0.5) mm and a height of (12.5±0.5) mm was prepared and placed in a compression set device with a compression rate set to 25%. The compression set test was carried out in a hot air aging box (model GT-7017-EMU) produced by High Speed Rail Testing Instruments (Dongguan) Co., Ltd. The temperature of the hot air aging box was set to 175°C and the test time was 22 hours. After the test, the specimen was restored to the standard laboratory temperature for (30±3) min and then the compression set rate was tested. The number of specimens was 3 and the median value was taken as the test result.
[0075] Solvent resistance: According to the provisions of GB / T 1690-2010, GB / T 531.1-2008 and GB / T 7759.1-2015, the following specimens were prepared: (a) Shore A hardness test specimen; (b) a square specimen with a thickness of (2.0±0.2) mm and a side length of 25 mm; (c) a cylindrical specimen with a diameter of (29.0±0.5) mm and a height of (12.5±0.5) mm. All the specimens were immersed in the test liquid in the test container and the solvent resistance was tested in a hot air aging box (model GT-7017-EMU) produced by High Speed Rail Testing Instruments (Dongguan) Co., Ltd. The temperature of the hot air aging box was set at 150°C, the test time was 70 hours, the test liquid was AMS 3021 test oil, and the number of specimens was 3. After the test, the specimens were placed at the standard laboratory temperature for 30 minutes, and then the Shore A hardness, volume change rate, and compression permanent deformation properties were tested.
[0076] The test results are shown in Table 1 and Table 2. In the table, “ / ” means that the property has not been tested yet, and “-” means that the material does not meet the conditions for testing this property and there is no value.
[0077] Table 1 Performance data of fluorosilicone rubber composite materials of Examples 1 to 6 Table 2 Performance data of fluorosilicone rubber composite materials of Comparative Examples 1 to 8 According to the material performance data of Examples 1 to 6 and the material performance data of Comparative Examples 1 to 8 in Table 1, it can be concluded that: It can be analyzed from Example 1, Example 2 and Comparative Example 1 that with the addition of reinforcing filler content, the tensile stress of the material is continuously improved. When the filler is added to 13 parts by mass, the modulus of the material reaches the technical requirements of the rubber ring for the rubber-plastic sealing composite structure. It can also be seen from the mechanical properties that the compression set rate of the material is constantly increasing. This is because with the increase of the filler content, the agglomeration phenomenon of the filler in the rubber matrix is also becoming more and more serious, so the resilience is reduced and the compression set performance is deteriorated, but this compression set rate is still at a low level, which shows that the sealing performance of the material is always guaranteed. For the tensile strength of the material, although it can be seen that the tensile strength is continuously reduced with the addition of the filler content, from the application scope of the present material invention, the present material is mainly used in the preparation of the sealing ring, so the tensile strength is not the performance that the present material focuses on, and the tensile strength of this material can also guarantee the normal operation of the material. In the test of the oil resistance of the material in the present invention, a new test solvent (test oil that meets the AMS 3021 standard) is selected to perform oil resistance test on the material. This test oil is highly polar and can be used as a reference test oil for hydraulic oil or aviation fuel with strong polarity used in today's military aircraft in extreme low temperature environments. This test method can better describe the advantages and disadvantages of the oil resistance of the material in extreme environments. It can be concluded from the data in the table that the fluorosilicone rubber composite material of the present invention has excellent oil resistance. After a long-term oil immersion test at a high temperature of 150°C@70h, the hardness change of the material is still maintained at about -4, and the volume change rate is still maintained at about 5%. In the research process, it is found that after the material is subjected to an oil immersion test at 150°C@70h, the compression permanent deformation rate of the material is 16%, which indicates that the material has excellent oil resistance and sealing performance.
[0078] It can be analyzed from Example 2 and Comparative Example 2 that after the hydroxyfluorosilicone oil is removed from the system, the elongation at break of the material decreases significantly, which indicates that the hydroxyfluorosilicone oil plays an important role in improving the dispersibility of the reinforcing filler in the matrix and reducing the degree of agglomeration of the reinforcing filler in the matrix.
[0079] It can be analyzed from Example 3, Comparative Example 3 and Comparative Example 4 that the vulcanizing agent TAIC mainly plays the role of auxiliary crosslinking and promoting vulcanization in the system. With the addition of the content of the vulcanizing agent TAIC, the modulus of the material continues to rise, but adding too much will lead to too low elongation at break of the material. This Example 3 meets the material's requirements for modulus, and compared with Example 1, the hardness of the material prepared in this example is also reduced, the compression permanent deformation rate is significantly reduced, and the sealing performance is better. After high-temperature oil immersion test, the hardness change of the material is also lower.
[0080] It can be analyzed from Example 4, Comparative Example 5 and Comparative Example 6 that after adding microcrystalline wax, the modulus of the material decreases and the elongation at break increases, indicating that the microcrystalline wax plays the role of a small molecule plasticizer in the matrix, while in Comparative Examples 5 and 6, replacing the processing aid with microcrystalline wax by stearic acid and using stearic acid and zinc oxide together does not improve the dispersion of the filler, and after the material is vulcanized at high temperature, the compression permanent deformation rate of the material deteriorates sharply, and the sealing performance deteriorates greatly, which indicates that the processing aid stearic acid system may not be suitable for the fluorosilicone rubber system.
[0081] It can be analyzed from Example 5, Comparative Example 7 and Comparative Example 8 in the study of the mixing preparation method of the material that when the rotor speed of the kneader is 60r / min, the mixing temperature in the closed chamber is 111°C. At this temperature, the in-situ modification effect of the reinforcing filler, the structuring control agent and the rubber matrix is poor. When the rotor speed of the kneader is 100r / min, the mixing temperature in the closed chamber is 150°C. Under this temperature and high shear, the material may suffer structural damage, thereby causing a decrease in the mechanical properties of the material. It was found that when the rotor speed of the kneader is 80r / min, the mixing temperature in the closed chamber is 130°C, and the material has the best performance at this time.
[0082] Compared with the prior art, the composite material provided by the present invention has the following advantages: (1) The combination of dipentadienyl vulcanizer and co-vulcanizer TAIC has a significant improvement effect on the three-dimensional network structure formed by the vulcanization of the rubber matrix.
[0083] (2) The addition of silane coupling agents is beneficial to optimizing the vulcanization cross-linking structure of the material. The molecular structure of some silane coupling agents is divided into two parts: one end contains a functional group that can be hydrolyzed into a hydroxyl group (such as methoxy, ethoxy), and the other end is an organic functional group (such as vinyl). In the rubber matrix, one end of the silane coupling agent can connect to the reinforcing filler to form a chemical or physical cross-linking; the other end combines with the rubber molecular chain through the addition reaction of the vinyl group to form an organic matrix-silane coupling agent-inorganic matrix bonding layer. On the one hand, it improves the dispersion of the reinforcing filler in the rubber matrix and reduces the degree of agglomeration of the filler. On the other hand, the silane coupling agent also increases the modulus of the material and optimizes the cross-linking structure.
[0084] (3) The reinforcing filler silica is pre-treated with hydroxyl fluorosilicone oil. On the one hand, hydroxyl fluorosilicone oil plays a role in structural control. The hydroxyl groups in hydroxyl fluorosilicone oil can form hydrogen bonds with the silanol groups on the surface of silica, and can also form hydrogen bonds with the oxygen atoms on the molecular chain of fluorosilicone rubber, playing a bridging role, enhancing the compatibility of the filler molecules in the rubber matrix, so that silica can be better dispersed in fluorosilicone rubber, while shielding some hydroxyl groups on the surface of silica, reducing the agglomeration defect effect of silica; in addition, hydroxyl fluorosilicone oil acts as a plasticizer in the form of small molecules, reducing the interaction force between the molecular chains of fluorosilicone rubber, enhancing the slippage of the molecular chains, and thus improving the tensile and rebound capabilities of the material.
[0085] (4) In the preparation method, the reinforcing filler treated with hydroxyfluorosilicone oil and silane coupling agent is added to the kneader and mixed at 130-140°C for 10 minutes. The reinforcing filler is added twice. First, 3 / 4 of the total amount of filler is added and mixed for 5 minutes. Then, the remaining filler is added and mixed for 5 minutes. During the two mixing processes, the upper top plug is intermittently opened and held for 0.5 minutes before closing the upper top plug, which helps to mix the filler more evenly.
[0086] (5) In the test method for oil resistance of the present invention, the oil resistance of the material is tested in a high temperature environment using a highly polar oil that complies with the AMS 3021 standard test standard. This test method can better describe the oil resistance performance of the material in an extremely high temperature and polar oil medium environment, thereby more accurately evaluating the applicability of the material for use in aircraft.
[0087] In summary, the high oil resistance and wide temperature range fluorosilicone rubber composite material prepared by the present invention has excellent oil resistance and sealing performance, can be used for a long time at -55°C to 200°C, and has important application prospects in combined sealing structures. It is mainly used in engine seals, fuel system seals, hydraulic system seals, dynamic surface seals, etc. on aircraft in the aerospace field.
Claims
1. A highly oil-resistant and wide temperature range fluorosilicone rubber composite material, characterized in that: The fluorosilicone rubber composite material is prepared from the following raw materials in parts by weight: 100 parts of fluorosilicone rubber masterbatch, 5 to 20 parts of reinforcing filler, 0.5 to 2 parts of vulcanizing agent, and 0.5 to 3 parts of structuring control agent.
2. The high oil-resistant and wide temperature range fluorosilicone rubber composite material according to claim 1, characterized in that: It also includes one or more of 0.5 to 3 parts of a processing aid, 0.5 to 3 parts of a silane coupling agent, and 0.1 to 0.5 parts of a vulcanizing agent.
3. The high oil-resistant and wide temperature range fluorosilicone rubber composite material according to claim 1, characterized in that: The fluorosilicone rubber masterbatch is a fluorosilicone rubber masterbatch prepared by blending fluorosilicone raw rubber, inorganic filler and silicone rubber; the fluorosilicone raw rubber is a fluorosilicone rubber prepared by a copolymer of 3,3,3-trifluoropropylmethylsiloxane chain segments and methylvinylsiloxane chain segments.
4. The high oil-resistant and wide temperature range fluorosilicone rubber composite material according to claim 1, characterized in that: The reinforcing filler is one or more of precipitated silica VN3, fumed silica A200, fumed silica R974, carbon black N330, carbon black N550, carbon black N774, carbon black N990, clay, calcium carbonate, and nano-light calcium carbonate, and the added amount is 10 to 15 parts by mass.
5. The high oil resistance and wide temperature range fluorosilicone rubber composite material according to claim 1, characterized in that: The vulcanizing agent is at least one of dibenzoyl peroxide (DCP), 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane (DBPH), 2,4-dichloroperoxybenzoyl (DCBP) and 1,1-di-tert-butylperoxy-3,3,5-trimethoxycyclohexane (3M).
6. The high oil resistance and wide temperature range fluorosilicone rubber composite material according to claim 2, characterized in that: The co-vulcanizing agent is at least one of triallyl cyanurate (TAC) and triallyl isocyanurate (TAIC).
7. The high oil resistance and wide temperature range fluorosilicone rubber composite material according to claim 2, characterized in that: The silane coupling agent is one or more of vinyl triethoxysilane (A151), 3-(methacryloyloxy)propyl trimethoxysilane (A174), and octyl triethoxysilane (A137).
8. A method for preparing a highly oil-resistant and wide-temperature-range fluorosilicone rubber composite material according to any one of claims 1 to 7, characterized in that: The preparation method comprises: S1 pretreatment: adding the structure control agent to the reinforcing filler and preliminarily mixing; S2 mixing: put the fluorosilicone rubber masterbatch and the pretreated reinforcing filler into a kneader and knead them under closed conditions. The kneading time is 10-25 minutes, the kneader speed is 60-100 r / min, the temperature is 130-140°C, and then the vulcanizing agent is added. The dispersion time is 10 minutes to obtain a mixed rubber; S3 secondary mixing: after the rubber mix obtained in the kneading machine is taken out, a secondary mixing operation is performed on an open rubber mixer. The secondary mixing operation includes thinning and triangular wrapping the rubber mix on the open rubber mixer. The roller distance is 0.1-2 mm, and the number of times is 1-2 times and 3-5 times respectively. Then the roller distance of the open rubber mixer is increased to 1-2 mm, and the roll is rolled out 3-4 times; S4 vulcanization: the mixed rubber after the secondary mixing is placed at room temperature for 16 hours and then vulcanized at a vulcanization temperature of 170°C. At this vulcanization temperature, the vulcanization time is 7 minutes and the vulcanization pressure is 15 MPa to obtain a vulcanized rubber; S5 secondary vulcanization: performing secondary vulcanization treatment on the vulcanized rubber, the secondary vulcanization temperature is 200° C., at this temperature, the secondary vulcanization time is 4 hours, and the fluorosilicone rubber composite material is obtained.
9. The preparation method according to claim 8, characterized in that In the S1 pretreatment step, a silane coupling agent is added together with a structuring control agent to the reinforcing filler and preliminarily mixed; and / or, in the S2 mixing step, a processing aid is added together with the fluorosilicone rubber masterbatch and the pretreated reinforcing filler is put into a kneader for kneading; and / or, in the S2 mixing step, a vulcanizing agent is added while a vulcanizing co-agent is added.
10. Use of the highly oil-resistant and wide-temperature-range fluorosilicone rubber composite material according to any one of claims 1 to 7 in a rubber-plastic combined oil-resistant sealing structure.
Citation Information
Patent Citations
Preparation method of fluorosilicone rubber / silicon rubber blend rubber for automotive high-voltage ignition wire
CN103436037A
Preparation method of high-corrosion-resistance external rubber pipe of hydraulic oil pipe
CN104962083A
Fluorosilicone rubber compound and preparation method thereof
CN111808430A
Solvent-resistant fluorinated silicone rubber sealing strip and preparation method thereof
CN111849172A
High-conductivity oil-resistant fluorosilicone composite rubber and preparation method thereof
CN115637049A
Cited By
Vibrating diaphragm for sound production device, sound production device and electronic equipment
CN120602851A